2020
DOI: 10.1029/2019jd032037
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric Bore Evolution and Instability Dynamics Observed in PMC Turbo Imaging and Rayleigh Lidar Profiling Over Northeastern Canada on 13 July 2018

Abstract: Two successive mesospheric bores were observed over northeastern Canada on 13 July 2018 in high‐resolution imaging and Rayleigh lidar profiling of polar mesospheric clouds (PMCs) performed aboard the PMC Turbo long‐duration balloon experiment. Four wide field‐of‐view cameras spanning an area of ~75 × 150 km at PMC altitudes captured the two evolutions occurring over ~2 hr and resolved bore and associated instability features as small as ~100 m. The Rayleigh lidar provided PMC backscatter profiling that reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 70 publications
5
30
2
Order By: Relevance
“…PMC imaging also has the ability to see very small features, even finer (below 20 m pixel resolution) than the best current airglow imaging. PMC imaging is hampered, though, by the thickness of the brightest portion of the PMC, often a km thick or less (Fritts et al, 2020), that lessens the chance of PMC imaging revealing the entire vertical extent of the instability.…”
Section: Introductionmentioning
confidence: 99%
“…PMC imaging also has the ability to see very small features, even finer (below 20 m pixel resolution) than the best current airglow imaging. PMC imaging is hampered, though, by the thickness of the brightest portion of the PMC, often a km thick or less (Fritts et al, 2020), that lessens the chance of PMC imaging revealing the entire vertical extent of the instability.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in Fig. 7 and in more detail in the overview paper by Fritts et al (2019) and the study by Fritts et al (2020), lidar measurements acquired by the BOLIDE instrument during the PMC Turbo mission yielded high-resolution backscatter profiles of PMC. All requirements (see Table 1) were met, and the performance surpassed that of the largest ground-based lidar systems.…”
Section: Discussionmentioning
confidence: 74%
“…We note that Kaifler et al (2013) and Ridder et al (2017) present PMC backscatter profiles at higher resolution of 30 s and 40 m, but no information on the detection threshold is given. A subset of the data in Kaifler et al (2013) is shown at a resolution of 0.33 s × 25 m. We want to highlight that BOLIDE data can be processed at even higher resolutions, albeit at the cost of a higher detection threshold as compared to the standard resolution of 30 s × 100 m. Examples with a resolution of 10 s × 20 m are presented in Fritts et al (2020). Figure 8 demonstrates the high-resolution capabilities of the BOLIDE instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have published an overview paper ( Fritts et al, 2019 ), describing GWs, associated instabilities, and the larger atmospheric context of our observations. We have also published a study of two successive mesospheric bores imaged by PMC Turbo ( Fritts et al, 2020 ). The PMC Turbo hardware enabled analysis on an area of ~75 × 150 km over ~2 hr while also resolving the bore and instability features with scales down to ~100 m. This allowed for improved resolution of bore dynamics relative to ground-based observations.…”
Section: Preliminary Resultsmentioning
confidence: 99%